Paying for Protection: The Effects of Having an Elite Left Tackle - Quinn Andrew Wesley Keefer (Journal of Applied Sports Management, 2017)
We exploit relatively new data collected by the NFL, since 2009, on the number of hits taken by a team’s quarterback to estimate the benefits and costs of employing an elite left tackle. We model the effect of an elite left tackle using a system of equations, which is estimated with seemingly unrelated regressions. Our system of equations considers quarterback hits, yards gained, and the probability of a quarterback injury. Overall, an All-Pro left tackle increases offensive production by 106 yards, or 8.5 points, and reduces the probability a team’s quarterback misses a game due to injury by 10.3 percentage points. However, the estimated compensation premium for elite left tackles is 1,151,000 to 1,528,000. Furthermore, the cost of an elite left tackle is far greater than the cost associated with an equal increase in points scored acquired through the running back market. Taken together; our results suggest elite left tackles are valued far above their expected contribution to offensive production due to the very large reduction in quarterback injury risk.
Keywords: Left tackle; quarterback protection; points scored; compensation premium